DEVELOPING RESEARCH SKILLS IN FUTURE COMPUTER SCIENCE TEACHERS - Toishybek, T.T.; Malikova, N.T.; Kassekeyeva, A.B.; Erekeshova, M.M.; Abugaliyeva, G.S. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The purpose of this study is to identify the need to develop pedagogical research skills among future computer science teachers. The objectives of the study include the analysis of modern methods and approaches to the development of these skills, as well as assessment of their impact on the quality of the educational process. The research methodology is based on the use of qualitative and quantitative methods, including surveys, interviews and analysis of teaching practice. The results of the study show that the development of research skills among future computer science teachers helps improve their professional competence, improve the quality of teaching and introduce innovative teaching methods. This study is significant for science, as it highlights the need to integrate research methods into the teacher training process, which in turn contributes to more effective and high-quality education in the field of information technology